miR-107 modulates EMT progression of OSCC by targeting SNCG and inhibiting the ERK/NF-κB signaling pathways - Han Liu; Jun Zheng; Zuodong Ren; Kangyuan Shen; Yan Zeng (Journal of Translational Medicine)
Abstract Background Oral squamous cell carcinoma (OSCC) is marked by aggressive metastasis and poor prognosis, with epithelial-mesenchymal transition (EMT) serving as a pivotal process in tumor metastasis. Consequently, identifying critical targets and elucidating the underlying mechanisms that drive OSCC metastasis are vital for enhancing patient prognosis. This study sought to clarify the significance and underlying molecular mechanisms of the miR-107/synuclein gamma (SNCG) axis in the regulation of OSCC migration, invasion, and EMT progression. Methods Peripheral blood from 26 OSCC patients and 24 controls assessed miR-107 expression, with GEO analysis for clinical significance. The effects of miR-107 and SNCG on OSCC migration, invasion and EMT in vivo and in vitro were assessed via wound healing, Transwell assays, qRT-PCR, WB and xenograft model. Results miR-107 was downregulated, while SNCG was upregulated in OSCC tissues. miR-107 served as a direct regulator of SNCG, leading to its downregulation. Gain- and loss-of-function studies demonstrated that SNCG promoted OSCC cell migration, invasion and EMT progression, while miR-107 inhibited EMT and exerted the opposite effect. These findings were confirmed in a nude mouse model, where miR-107 counteracted SNCG-induced tumor growth and EMT progression. Mechanistically, SNCG increased ERK1/2 and NF-κB p65 phosphorylation without altering total protein levels, while miR-107 mimic partially reversed these effects, suggesting that the miR-107/SNCG axis regulates migration, invasion and EMT progression through the ERK1/2 and NF-κB pathways. Conclusions Overall, our findings elucidated that miR-107 attenuated migration and EMT in OSCC by targeting SNCG and inhibiting the ERK1/2/NF-κB pathway, providing novel potential therapeutic targets for OSCC.